FENOMENA KEADILAN DALAM PENGENAAN SANKSI PERPAJAKAN: ANALISIS PENEGAKAN HUKUM PAJAK DI INDONESIA - Putri, Rita Dwi; Das, Nidia Anggreni; Sukraini, Juita; Daniati, Yusmi; Aprilia, Dara; Wulandari, Jingga; Risanti, Dezy Risanti (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2025)
Tax law enforcement is one of the main pillars in maintaining the sustainability of state revenue. Sanctions in taxation are an important tool in the tax law system in Indonesia that aims to increase compliance and provide a deterrent effect for taxpayers who violate the rules. However, the application of these sanctions is often the subject of debate, especially regarding whether the sanctions given are in line with the principles of justice. In practice, the application of sanctions is not always consistent and proportionate, thus giving rise to a view of injustice, especially for taxpayers who experience limitations in access to information and legal resources. This study aims to examine the phenomenon of injustice in the provision of tax sanctions by examining juridical and ethical aspects in tax law enforcement in Indonesia. The methods used are literature studies from tax regulations, scientific journals, and empirical studies on taxpayer perceptions and behaviors. The results of the study show that there is a discrepancy between positive legal rules that regulate sanctions normatively and practices in the field that often ignore the principles of substantive justice and law enforcement ethics. Factors that cause this imbalance include a lack of socialization of regulations, a lack of understanding of taxpayers of their rights and obligations, and the potential for abuse of authority by tax officials. Therefore, reforms are needed in the design and implementation of tax sanctions that not only focus on fiscal aspects, but also ensure procedural fairness, transparency, and legal protection for taxpayers. The research recommends a more humane, proportional, and ethical-based approach to law enforcement as an effort to increase public trust in the national tax system.